The design of the avian respiratory system: development and morphology - a review - A.D. Firdous, (Indian Journal of Veterinary and Animal Sciences Research, 2025)
By every definition birds are extreme animals with singular adaptive morphologies and physiologies.The respiratory system is a good model for studying optimization from a functional perspective because it consists of linked structures with defined design parameters and an overall function that has a measurable upper limit, the maximum rate of oxygen consumption. The investigations of the respiratory tract concentrate on several aspects, viz. bioacoustics, neuroanatomical, respiratory physiology, morphological-ecological analysis of the relation of the respiratory tract structure to the life habits and rarely on the developmental descriptions. The evolution of the vertebrate respiratory system achieved its most efficient state in birds, with their constant volume parabronchial lungs and highly compliant air sacs having low pressure ventilation. These additional characteristics equipped the birds for sustained flight or buoyancy in water. The respiratory organs of birds differ from those of mammals in a number of specific features which are partly associated with the requirements of flight and the great work load that this form of locomotion demands, and partly with the voice production. Differences in the development of this system do exist among different orders or species or even birds of same species.